GEOCHEMISTRY OF ISOTOPES OF CARBON, OXYGEN, AND RARE-EARTH ELEMENTS IN METASEDIMENTS OF THE OL'KHON METAMORPHIC COMPLEX (WESTERN PREBAIKALIA) - Makrygina V.A.; Petrova Z.I.; Ponomarchuk V.A.; Smirnova E.V.; Sandimirova G.P.; Bobrov V.A. (My University, 2000)
The isotopic compositions of carbon, oxygen, and strontium in marbles and quartzites in various metamorphic zones of the Ol'khon metamorphic complex and the REE patterns of these rocks prove that the source rocks of the latter formed in a shallow-sea environment under reducing conditions preventing a complete loss of organic relics. The variations in carbon isotope ratio in graphites and calcites of marbles are related to isotope exchange between these minerals with increasing temperature of regional metamorphism. The carbonate-free metasediments are most similar in isotopic composition of carbon to biogenic source rocks.